Finite element thermal analysis of a lateral microelectrothermal actuators / Mohd Shukhri Abd Rahman - Abd Rahman, Mohd Shukhri (2011)
Nowadays, MEMS is an enabling technology allowing the development of smart products, augmenting the computational ability of microelectronics with the perception and control capabilities of microsensors and microactuators and expanding the space of possible designs and applications. Microelectrothermal actuators are one of the most attractive micro-moving actuators as they can deliver large forces and displacements compared to other types of actuators such as piezoelectric and electrostatic actuators. These thermal actuators are used to move micro device, such as ratchets and gear trains. Array of thermal actuators can be connected together at their blade tips to multiply the effective force. This study reports on the investigation to design, and characterize a lateral Microelectrothermal actuator using ANSYS in order to simulate. The aim was to compute and compare the blade tip displacement for an applied potential difference across the electrical connection pads, obtain the total current and heat flow performance of the differences material at the same operation conditions. The simulations reported here were performed with the best available data. It is important to note that a slightly different material property data will change the behavior of the devices slightly. However, with a suitable modification of the shape, the same performance for example displacement can be achieved with the new material property data.